Shoot and Root Responses to Water Deficits in Rainfed Lowland Rice - Cruz, R.T.; O'Toole, J.C.; Dingkuhn, M.; Yambao, E.B.; Thangaraj, M.; De Datta, S.K. (Commonwealth Scientific and Industrial Research Organisation, 1986)
A field study was conducted to determine the response of the rice cultivar IR54 to a gradient of soil moisture conditions imposed for 19 days at the vegetative stage using a line source sprinkler system. A mild plant water stress at the vegetative growth stage decreased tiller number, leaf area index (LAI), apparent canopy photosynthetic rates, leaf nitrogen per unit land area, shoot and total root dry mass, and total root length density. After complete stress relief by reflooding, LAI and crop growth remained below that of unstressed plants. The lower cumulative assimilation per unit land area in the stressed treatments resulted in reduced shoot and root dry matter yields and lower grain yields. Water stress increased the ratio of shoot dry mass to root dry mass, and the ratio of leaf area to total root length. The decrease in root length was attributed to increased soil mechanical impedance.